Unanimous Constitutional Consent and the Immigration Problem - Stefan D. Josten; Klaus W. Zimmermann (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2004)
This paper utilizes the cross-cutting cleavages approach to evaluate the probability of a unanimous constitutional consent and, based on these results, discusses the implications of immigration on an existing constitutional consent. It is shown that previous conclusions of beneficial effects stemming from a multitude of political dimensions for a unanimous constitutional consent crucially depend on the assumption of an extreme mode of intrapersonal compensation of constitutional majority and minority preferences. These conclusions are reversed once you consider more restrictive schemes of such intrapersonal compensation. Since, furthermore, the probability of constitutional consent unambiguously falls with a growing size of the collectivity, only a policy of selective and controlled immigration will be able to guarantee with regard to the existing cleavages of a society that the existing constitutional consent will not be damaged or destroyed, whereas uncontrolled immigration, possibly based on ethical norms, will risk the breakdown of any constitutional consent in a society.
urn:nbn:de:gbv:705-opus-16504
Keywords: K10; H41; H10; 330; Verfassungsökonomik; Einwanderung; Sozialvertrag; Theorie